KOMUNIKASI ANTARBUDAYA DALAM ADAPTASI MAHASANTRI BARU ASAL MADURA DI LINGKUNGAN PESANTREN - Momon Halpaleya; Tawvicky hidayat (Ma'had Aly Journal of Islamic Studies, 2026)
Intercultural communication plays an important role in the adaptation process of new students in Islamic boarding schools. Differences in language, culture, customs, and communication styles often become obstacles for students from different regions. This study aims to analyze the adaptation process of new mahasantri from Madura in the pesantren environment through the perspective of intercultural communication, identify communication barriers, and describe adaptation strategies carried out by mahasantri. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The findings indicate that intercultural communication helps mahasantri build social relationships, exchange experiences, and understand cultural differences among students from various regions. The adaptation process is carried out through active interaction, sharing experiences, and mutual understanding among mahasantri. The main communication barriers experienced by mahasantri are shame, lack of confidence in starting conversations, language differences, and different communication styles. However, openness, tolerance, and intensive interaction are able to support successful adaptation in pesantren life. This study concludes that intercultural communication has an important role in creating harmonious social relationships and supporting the adaptation of new mahasantri in multicultural pesantren environments.